Effect mechanism of exit-water temperature distribution characteristics on the anti-freezing of natural draft dry cooling tower. (October 2019) - Li, Wendong; Wang, Huitao; Wang, Jian; Duan, Chongpeng; Zhao, Yuanbin
Highlights: The critical anti-freezing averaged exit water temperature of NDDCT was studied. A full scale 3D numerical model of a NDDCT was developed and validated. The exit water temperature distributions was studied from column to whole tower. The anti-freezing criterion was obtained in different working conditions. Abstract: For thermal power plants with natural draft dry cooling towers (NDDCTs) in arid and severely cold regions, the anti-freezing of finned-tube bundles is critical for the safe and economic running of a thermodynamic system. Using volume source term models representing the water flow in each pass of a cooling column, a 3D numerical model for NDDCT was established and validated. The exit water temperature and its relevant distribution characteristics could then be analyzed from cooling columns, deltas to the whole tower. Based on the analyses, the non-equilibrium temperature difference and relevant anti-freezing parameters were defined. It could be observed that the ambient crosswind, ambient temperature, heat load, circulating water flow rate, and convection pattern have different impact mechanisms on the exit water temperature distribution characteristics, among which, the ambient crosswind plays a major role but the ambient temperature has a negligible effect. Finally, the critical anti-freezing average exit-water temperatures were presented based on real work conditions, which would facilitate the safe and economic operation of NDDCTs in severely cold weather.